2005
DOI: 10.1038/sj.bjc.6602334
|View full text |Cite
|
Sign up to set email alerts
|

Ascitic complement system in ovarian cancer

Abstract: Ovarian cancer spreads intraperitoneally and forms fluid, whereby the diagnosis and therapy often become delayed. As the complement (C) system may provide a cytotoxic effector arm for both immunological surveillance and mAb-therapy, we have characterised the C system in the intraperitoneal ascitic fluid (AF) from ovarian cancer patients. Most of the AF samples showed alternative and classical pathway haemolytic activity. The levels of C3 and C4 were similar to or in the lower normal range when compared to valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 46 publications
(61 reference statements)
4
92
1
1
Order By: Relevance
“…Subsequent analysis of an independent sample set confirmed an increase of the 8.1 and 8.9 kDa C3a fragments in breast cancer (Li et al, 2005), which was confirmed by a third study (Mathelin et al, 2006). Finally, C3a desArg is not unique to breast cancer and has been shown to be elevated in other cancers, such as ovarian cancer (Bjorge et al, 2005), chronic lymphoid malignancies (Miguet et al, 2006), hepatocellular carcinoma (Lee et al, 2006) and colon cancer (Ward et al, 2006). We also identify, for the first time, PF-4 as Serum protein signature and detection of DCIS J Solassol et al a potential biomarker in early-stage breast cancer.…”
Section: Discussionsupporting
confidence: 53%
“…Subsequent analysis of an independent sample set confirmed an increase of the 8.1 and 8.9 kDa C3a fragments in breast cancer (Li et al, 2005), which was confirmed by a third study (Mathelin et al, 2006). Finally, C3a desArg is not unique to breast cancer and has been shown to be elevated in other cancers, such as ovarian cancer (Bjorge et al, 2005), chronic lymphoid malignancies (Miguet et al, 2006), hepatocellular carcinoma (Lee et al, 2006) and colon cancer (Ward et al, 2006). We also identify, for the first time, PF-4 as Serum protein signature and detection of DCIS J Solassol et al a potential biomarker in early-stage breast cancer.…”
Section: Discussionsupporting
confidence: 53%
“…Colon Cancer Cells Produce C5a-The complement system can recognize tumor cells, and complement deposition is observed in different types of tumors (9,15). Cells from some tumor types under serum-free conditions will activate and release C5a.…”
Section: Resultsmentioning
confidence: 99%
“…We found chain F; human complement component C3c to be 1.53-fold increased in squamous cell carcinoma sera. Two recent reports have shown that elevated levels of C3a were found in the ascitic fluids of ovarian cancer patients and in patients with chronic hepatitis C/HCV-related HCC [14,15].…”
Section: Discussionmentioning
confidence: 99%